Rainwater as a potential alternative source of water in Tanjong Malim, Perak - Che Ngah Mohamad Suhaily Yusri, Othman Zainudin, Hashim Mohmadisa, Nayan Nasir, Saleh Yazid (N/A, 2014)
Rainwater as a potential alternative source of water in Tanjong Malim, Perak by Che Ngah Mohamad Suhaily Yusri, Othman Zainudin, Hashim Mohmadisa, Nayan Nasir, Saleh Yazid,